A description of the formation and growth processes of CaTiO3 mesocrystals: a joint experimental and theoretical approach. Issue 7 (14th July 2020) - Moreira, Mario L.; Bordin, José Rafael; Andrés, Juan; Varela, José A.; Longo, Elson
Abstract : We report a combined experimental and theoretical study to rationalize the self-assembly mechanism of CaTiO3 mesocrystals through microwave-assisted hydrothermal synthesis. Abstract : In this paper, we report on a combined experimental and theoretical study conducted in order to rationalize the formation and growth mechanism of CaTiO3 mesocrystals through the microwave-assisted hydrothermal synthesis over short times. The transformation process in which the initial nanoplates are converted to microcube-like CaTiO3 is investigated in detail. Field emission scanning electron microscopy, photoluminescence emission analysis and Langevin dynamic simulations were carried out. We determined how the quenching rate induced by microwave irradiation can be used to finely tune the structural characteristics of the final CaTiO3 nanoparticles, including size, shape and crystallinity, showing that the microcube-like particles appear only within a temperature range of 130–200 °C. The theoretical and experimental results allow us to propose a mechanism involving three steps: i) a nucleation process of nanoplates below 10 min, ii) a self-assembly process of nanoplates to form microcube-shaped CaTiO3 under specific thermodynamic conditions, and finally, iii) the formation of microcube-like shapes as the result of a long assembly process. The present results not only provide a deeper insight into the nucleation and growth processes, but also help to find a relationship between morphology and photoluminescence behavior throughout the microwave-assisted hydrothermal synthesis of target metal oxides. These findings shift the focus of the experimental and theoretical research onto the detailed study of the connectivity of TiO6 octahedra and CaO12 cube-octahedra as the constituent building blocks of the CaTiO3 lattice, paving the way for quantitative predictions of the events involved in the self-assembly processes of CaTiO3 nanocrystals.